Bile Acid Determination after Standardized Glucose Load in Pregnant Women - Adams, April; Jacobs, Katherine; Vogel, Rachel Isaksson; Lupo, Virginia (American Journal of Perinatology Reports, 2015)
Objective Intrahepatic cholestasis of pregnancy (ICP) is a rare liver disorder, usually manifesting in the third trimester and associated with increased perinatal morbidity and mortality. The hallmark laboratory abnormality in ICP is elevated fasting serum bile acids; however, there are limited data on whether a nonfasting state affects a pregnant woman's total bile acids. This study assesses fasting and nonfasting bile acid levels in 10 healthy pregnant women after a standardized glucose load to provide insight into the effects of a glucose load on bile acid profiles.Study Design Pilot prospective cohort analysis of serum bile acids in pregnant women. A total of 10 healthy pregnant women from 28 to 32 weeks' gestation were recruited for the study before undergoing a glucose tolerance test. Total serum bile acids were collected for each subject in the overnight fasting state, and 1 and 3 hours after the 100-g glucose load.Results There was a statistically significant difference between fasting versus 3-hour values. There was no statistically significant difference between fasting versus 1-hour and 1-hour versus 3-hour values.Conclusion There is a difference between fasting and nonfasting total serum bile acids after a 100-g glucose load in healthy pregnant women.
Keywords: bile acids; cholestasis; pregnancy; liver disease